Coronary Heart Disease, Diabetes, and Sexuality in Men. Issue 6 (1st June 2016) - Hackett, Geoff; Krychman, Michael; Baldwin, David; Bennett, Nelson; El-Zawahry, Ahmed; Graziottin, Alessandra; Lukasiewicz, Monika; McVary, Kevin; Sato, Yoshikazu; Incrocci, Luca
ABSTRACT: Erectile dysfunction (ED) has been well recognized as a marker of increased cardiovascular risk for more than 15 years, especially in younger men. Early detection of ED represents an opportunity to intervene to decrease the risk of future cardiovascular events and limit the progression of ED severity. Evidence suggests there is a window of opportunity of 3 to 5 years from the onset of ED to subsequent cardiovascular events. This opportunity is usually missed if the onus is placed on the patient to seek care for his sexual problems. Unfortunately, these clear messages have not been incorporated into routine cardiovascular care. The reasons for these disparities within specialties are discussed in this article, in addition to management algorithms. Lifestyle modification is usually recommended as the first-line treatment to correct ED and lessen cardiovascular risk, but evidence suggests that this might be effective only in men without established cardiovascular comorbidities. In men with type 2 diabetes mellitus and established cardiovascular disease, lifestyle modification alone is unlikely to be effective. Cardiovascular medications are often associated with sexual dysfunction but changes in medication are more likely to be beneficial in men with milder recent-onset ED. A balanced view must be taken related to medication adverse events, taking into account optimal management of established cardiovascular disease. Testosterone deficiency has been associated with different metabolic disorders, especially metabolic syndrome and type 2 diabetes mellitus. Testosterone deficiency syndrome has been associated with an independent burden on sexual function globally and increased cardiovascular and all-cause mortality. Testosterone replacement therapy has been shown to improve multiple aspects of sexual function and, in some studies, has been associated with a decrease in mortality, especially in men with type 2 diabetes mellitus. Recent studies have suggested that phosphodiesterase type 5 inhibitors, the first-line medications to treat ED, could decrease cardiovascular and all-cause mortality, through multiple mechanisms, predominantly related to improved endothelial function.